The Development of a Sign Language Detection System Using TensorFlow and CVzone - Dinda Putri Ramadani; Prayitno; Praditya Oktanza Djaduk Wibisono; Mochammad Rizky Abadi Sutoyo (Media Journal of General Computer Science, 2026)
Sign language is a communication system used to help deaf people interact with each other. In Indonesia, there are two main sign languages, namely Indonesian Sign Language (BISINDO) and Indonesian Sign Language System (SIBI), each of which has differences in the use of hands. This research develops a SIBI-based sign language recognition system using TensorFlow and CVzone. This system uses computer vision technology and machine learning to recognize SIBI alphabet hand gestures. The model is developed using a dataset captured by a camera and trained with TensorFlow to enable real-time gesture recognition, while CVzone facilitates effective gesture tracking. Test results show that the average accuracy in recognizing the SIBI alphabet reaches more than 90%, which reflects the system's good performance in recognizing the alphabet. It is expected that the accuracy of detecting hand gestures in sign language will be improved to support communication for the deaf community in Indonesia.